Does Restricting Access to Credit Affect Learning Outcomes? Evidence from a Regulatory Shock to Microfinance in India - Muneer Kalliyil; Soham Sahoo (Institute of Labor Economics (IZA), 2024)
This study examines how restricted access to microfinance by households affects children's learning outcomes, utilizing a unique natural experiment that halted all microfinance operations in Andhra Pradesh (AP), India, in 2010. The analysis exploits quasi-random variation in district-level exposure to the shock in states other than AP, as the regulation affected lenders' liquidity nationwide. Using difference-in-differences and event study designs, we find a significant and persistent decline in children's learning outcomes. The restoration of credit access does not fully reverse these effects, highlighting the long-term consequences of short-term financial disruptions. As plausible mechanisms, we find a shift in enrollment from private to government schools, lower household spending on education, reduced food expenditure impacting nutrition, and a decline in mothers' employment. Heterogeneity analysis reveals that the adverse effects were more prominent for girls and younger children. By focusing on the effects of regulatory restrictions rather than micro-finance service provision, this study complements existing literature and provides a more comprehensive understanding of the socioeconomic impacts of microfinance.
Keywords: E51; G21; G28; I2; J16; R51; 330; microfinance regulation; credit constraint; learning outcomes; schooling; education; India